2012
DOI: 10.5012/bkcs.2012.33.8.2560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polymer Characteristics on the Thermal Stability of Retinol Encapsulated in Aliphatic Polyester Nanoparticles

Abstract: The present study investigates how the thermal stability of retinol (vitamin A) encapsulated in polyester nanoparticles is influenced by the types of polyester used for the nanoparticles. A variety of polyester-retinol nanoparticles were prepared with various polyesters like: poly(ethylene adipate), PEA; poly(butylene adipate), PBA; poly(hexamethylene adipate), PHMA; and three polycaprolactones, PCL, of different molecular weights (M n ~10, 40, and 80K). C. More importantly, this study has also found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…As for the crystalline structures, as discussed in section , the amount of crystallites in the PCL10K14-PCG6-Drug2 nanoparticles were a little lower than the PCL10K7-PCG3-Drug1 nanoparticles. Although the melting temperature of PCL10K14-PCG6-Drug2 was higher by 1–2 °C, the temperatures were far away from the storage temperatures, which would negligibly affect the formation of drug crystals . Putting these factors together, it was suggested that the nanoparticle size is the dominant factor influencing the formation of the drug crystals for the two crystalline nanoparticles in these media.…”
Section: Resultsmentioning
confidence: 99%
“…As for the crystalline structures, as discussed in section , the amount of crystallites in the PCL10K14-PCG6-Drug2 nanoparticles were a little lower than the PCL10K7-PCG3-Drug1 nanoparticles. Although the melting temperature of PCL10K14-PCG6-Drug2 was higher by 1–2 °C, the temperatures were far away from the storage temperatures, which would negligibly affect the formation of drug crystals . Putting these factors together, it was suggested that the nanoparticle size is the dominant factor influencing the formation of the drug crystals for the two crystalline nanoparticles in these media.…”
Section: Resultsmentioning
confidence: 99%
“…RET as terpene alcohol has already been applied as the initiator of the ring-opening polymerization (ROP) of ethylene oxide [3] or lactide [4] resulting in welldefined biohybrid polymers with potential applications as liquid crystalline materials, amphiphilies, or conjugate systems targeted to stellate liver cells. However, according to the literature the delivery of RET is supported by encapsulation strategy, mostly into chitozan [5][6][7], and polyester (polyadipates, polycaprolactone) [8] nanoparticles. Moreover, spherical inorganic particles containing RET have been fabricated using silica in combination with surfactants and hydroxypropyl cellulose [9], tetraethyl orthosilicate sol-gel systems [10], or polyphosphates with calcium ions [11].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to enhanced stability, it has been previously demonstrated that the water vapor permeability of BMC (51) is lower than what is commonly used for preservation of fruits and vegetables (52); thus, it is likely that the known moisture barrier properties of BMC provide protection against humidity and small-molecule diffusion by acting as a physical barrier between the payload and the environment. The UV-protective abilities of BMC can likely be attributed to the increased refractive index due to encapsulation in BMC (53), which will lower light exposure to encapsulated micronutrients. BMC is soluble at low pH in aqueous solutions and in non-aqueous solvents; hence, the solubility of BMC enabled rapid dissolution and release in stomach conditions, thus providing the versatility to facilitate encapsulation of 11 distinct micronutrients.…”
Section: Discussionmentioning
confidence: 99%
“…5A). Cooking the encapsulated ferrous sulfate had no effect on its bioavailability [FIA, 1.41 (0.91, 2.19)%; RBV, 42 (34,53)%] (Fig. 5A).…”
Section: Bioavailability Of Iron In Humans and Iron Transport In An I...mentioning
confidence: 99%